2017
DOI: 10.1002/app.45318
|View full text |Cite
|
Sign up to set email alerts
|

Lignin nanoparticles by ultrasonication and their incorporation in waterborne polymer nanocomposites

Abstract: Lignin nanoparticles (nanolignin, NL) were prepared in this work by ultrasonic treatment of softwood kraft lignin to obtain lignin‐water dispersions with excellent colloidal stability. A thorough characterization of the chemical, physical, and morphological properties of the new NL particles allowed for direct comparisons with the untreated parent material. Such NL particles were incorporated into a waterborne thermoplastic polyurethane matrix at different concentrations to yield bio‐based nanocomposite materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 57 publications
4
54
2
Order By: Relevance
“…T g is directly related to the mobility of the macromolecular chains, which may be affected by a complex interplay between several factors including the molecular weight of the material, the presence of chemical or physical crosslinks, and the presence of strong intermolecular interactions between the macromolecular chains such as intermolecular hydrogen bonds [15]. Gupta et al [60] reported similar results for LPs produced from low sulfonated lignin (lignin protobind-1000) using acid precipitation method, where the T g value of LNPs (153.7°C) was higher than the T g of lignin (151.5°C).…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…T g is directly related to the mobility of the macromolecular chains, which may be affected by a complex interplay between several factors including the molecular weight of the material, the presence of chemical or physical crosslinks, and the presence of strong intermolecular interactions between the macromolecular chains such as intermolecular hydrogen bonds [15]. Gupta et al [60] reported similar results for LPs produced from low sulfonated lignin (lignin protobind-1000) using acid precipitation method, where the T g value of LNPs (153.7°C) was higher than the T g of lignin (151.5°C).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Nowadays, the development of NPs from lignin has gained interest, given its nature, for drug delivery systems [9][10][11], delivery of hydrophobic molecules [12], improvement of UV barrier [13,14], as reinforcing agent in nanocomposites [15], sorbents for heavy metal ions and other environmental pollutants, and antibacterial and antioxidant applications [16][17][18][19]. They have also been used as an alternative to inorganic NPs due to some safety issues raised in recent years [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a small part of the technical lignins produced worldwide is actually used for material manufacturing and chemical synthesis, as the majority is being burnt for energy recovery at the processing plant itself [8]. The main existing pathways for lignin valorization aim at its direct utilization (e.g., as micro or nanostructured filler in blend with polymers [9,10] or as a water-reducing agent for concrete [11]) with limited processing after the initial cellulose separation from the original biomasses. Lignin represents, however, a highly abundant natural aromatic feedstock with potentially very interesting applications in a sustainable economy scenario, especially considering the high primary production volumes and the inherently renewable nature of this resource [12].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The main pathways for lignin valorization typically aim for the production of materials including its use as a filler, in blend with polymers, as a copolymer, and as a water-reducing agent for concrete, allowing its direct exploitation without requiring a preliminary depolymerization step after the original biomass fractionation. 1116…”
Section: Introductionmentioning
confidence: 99%